Exploring Self Potential through Interest and Talent Assistance with the Implications of the ABCD Method for An-Nur MTS Students in Sawahan Village, Turen District, Malang Regency - Khoirul Umam; Dewi Khusnul Kharomah; M. Daffa Ajira Anjayna; Ainul Riski; Meisy Imroatus Sholichah; Ridho Wardhani; Shoha Salsabiela; Maureta Etna Riska S; Lalu Ibnu Sani Oktavio (Jurnal Pengabdian Masyarakat Bestari, 2023)
“Kuliah Kerja Mahasiswa (KKM)” is a community activity held by the State Islamic University of Maulana Malik Ibrahim Malang that the substance of this activity is the same as the “Kuliah Kerja Nyata (KKN)” in general.  KKM Group 159 of UIN Maliki Malang made MTs An-Nur Sawahan Village the target for carrying out community-themed work programs.  Focusing on extracurricular activities that still receive less attention so that students are confused about their interests and talents are the right targets for implementing the ABCD (Asset Based Community Development) method. The stages carried out are discovery, dream, design, and fate.  From these several stages it produces output in the form of Interest and Talent Seminars and AMB Gathering (An-Nur Looking for Talent) which besides aiming to explore potential, also to increase the self-confidence of MTs An-Nur students.